PELUANG DAN TANTANGAN BANK SYARIAH DI ERA PERBANKAN DIGITAL DALAM PERSEPKTIF GENERASI Z - Junaedi, Achmad Tavip; Renaldo, Nicholas; Yovita, Indri; Veronica, Kristy; Sudarno, Sudarno (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The rapid development of technology gave birth to digital banking, better known as digital banking. How to prepare Islamic banks to take opportunities and challenges in the digital era. Sharia banking in the city of Pekanbaru is experiencing a period of digitalization. This study uses a qualitative method as a phenomenological approach to identify opportunities and challenges for Islamic banks in the digital banking era. Information is aggregated through monitoring, debriefing, and voting. The results of this research create opportunities and challenges experienced by Islamic banks in the digital era, namely; 1) the relief experienced after the emergence of digital banking began as a relief for doing business without having to attend the bank directly. 2) Digital banking is a Sharia design based on the Islamic religion which is far from usury. 3) Accelerate the activities of Islamic banks in Malay, the customers. The challenges experienced by Islamic banks in the digital banking era were due to the high level of competition as conventional banks and the slow internet network which was always neglected. Perkembangan teknologi yang pesat melahirkan perbankan digital atau lebih dikenal dengan digital banking. Bagaimana mempersiapkan bank syariah dalam mengambil peluang dan tantangan di era digital. Perbankan syariah di kota Pekanbaru sedang mengalami masa digitalisasi. Penelitian ini memakai tata cara kualitatif sebagai pendekatan fenomenologis untuk mengenali kesempatan serta tantangan bank syariah di masa perbankan digital. Informasi digabungkan lewat pemantauan, tanya jawab, serta pemilihan. Hasil riset ini menciptakan kesempatan serta tantangan yang dialami bank syariah di masa digital, ialah; 1) keringanan yang dialami sesudah timbulnya digital banking dimulai sebagai keringanan berbisnis tanpa wajib menghadiri bank langsung. 2) Perbankan digital ialah rancangan syariah bersumber pada anutan agama Islam yang jauh dari riba. 3) Memesatkan aktivitas bank syariah di Melayu ini nasabahnya. Tantangan yang dirasakan bank syariah di masa perbankan digital ini diakibatkan tingginya tingkatan kompetisi sebagai bank konvensional serta lambatnya jaringan internet yang senantiasa terabaikan.